Experimental Oronasal Transmission of Chronic Wasting Disease Agent from White-Tailed Deer to Suffolk Sheep - Eric D. Cassmann (Centers for Disease Control and Prevention, 2021)
Chronic wasting disease (CWD) is a fatal prion disease of cervids. We examined host range of CWD by oronasally inoculating Suffolk sheep with brain homogenate from a CWD-positive white-tailed deer. Sixty months after inoculation, 1/7 sheep had immunoreactivity against the misfolded form of prion protein in lymphoid tissue. Results were confirmed by mouse bioassay.